Exploring the challenges to circular supply chain (CSC) implementation in the chemical-intensive manufacturing industries of emerging economies: Implications toward sustainability - BARI, A. B.M.Mainul; RAHMAN, Md Mahfujur; Raihan, Asif; MODIBBO, Umar Muhammad; TRIVEDI, Ashish; AMIN, Nuhu; TAGHIPOUR, Amirhossein (My University, 2025)
Waste management strategies employed by emerging economies worldwide are often insufficient to address the new-age sustainability challenges. Especially in chemical-intensive manufacturing industries, increasing levels of waste production are a significant environmental threat. Adopting a circular supply chain (CSC) can be a viable solution to this problem since it incorporates the components of the circular economy into an organization's supply chain, bringing an engaging viewpoint to the supply chain sustainability field. Nevertheless, the adoption of CSC in chemical-intensive manufacturing industries faces various intricate challenges in emerging economies. This study, therefore, aims to explore and evaluate the challenges associated with adopting CSC in the chemical-intensive manufacturing industries, using the empirical case of an emerging economy, Bangladesh. After a thorough literature review and expert validation, 26 challenges were analyzed using a probabilistic group decision-making approach, i.e., the Bayesian best-worst method (BWM). The result showed that the most significant challenge is the chemical composition-related complexity (global weight=0.0801), followed by strong emphasis on the take-make-dispose policy (0.0705), and insufficient investment and financial resources (0.0697). On the contrary, the least important challenge is the resistance toward the transition from conventional supply chain to CSC (0.0078). The outcomes of this study are expected to enrich existing knowledge and comprehension of the challenges linked to implementing CSC practices in Bangladesh and contribute to achieving Sustainable Development Goals (SDGs), such as SDG 3 (good health and well-being), SDG 11 (sustainable cities and communities), SDG 12 (responsible consumption and production), SDG 13 (climate action), and so on.
Keywords: Bayesian best-worst method (BWM); Chemical-intensive manufacturing industries; Circular economy (CE); Circular supply chain (CSC); Emerging economy; Sustainable Development Goals (SDGs)